Porównanie wpływu czynników społecznych na realizację dwóch potencjałów biologicznych: wzrostowego młodzieży oraz rozrodczego rodzin w Polsce - Szklarska, Alicja; Welon, Zygmunt (Polskie Towarzystwo Antropologiczne, 1996)
THE EFFECTS OF SOCIAL FACTORS ON TWO BIOLOGICAL POTENTIALS: GROWTH OF ADOLESCENTS AND REPRODUCTION IN POLISH FAMILIES. The purpose of the study is an examination of the hypothesis whether the influence of each of the three social factors (urbanization, education, and occupation) on attainments of two biological potentials: growth o f youth and fertility differ between each other. The results were based on two country-wide samples of military conscripts (1965, 1986), using the path analysis.
THE EFFECTS OF SOCIAL FACTORS ON TWO BIOLOGICAL POTENTIALS: GROWTH OF ADOLESCENTS AND REPRODUCTION IN POLISH FAMILIES